Early removal of the abdominal patch is superior to late removal in children with congenital diaphragmatic hernia - Riebesell, Kaja; Mohr, Christoph; Niklaus, Marina; Martel, Richard; Petroswky, Michaela Klinke; Weiß, Christel; Hoffmann, Jana; Riemer, Carolin; Schaible, Thomas; Zahn, Katrin; Halniyazova, Aylar; Boettcher, Michael; et al. (Journal of pediatric surgery, 2025)
Introduction - Open repair of Congenital diaphragmatic hernia (CDH) in neonates often involves reconstruction of the abdominal wall using a patch. Data on predictors for the need of a patch and associated postoperative risks, such as infection or patch detachment, are limited. Specifically, the question regarding the ideal timepoint of patch removal remains unanswered. - Methods - Data from 1000 neonatal CDH cases at the University Clinic Mannheim (2000-2022) were analyzed in this longitudinal, prospective cohort study. The study identified predictors for the requirement of an abdominal wall patch, quantified the surgical duration attributable to their use, determined outcome variables and investigated the incidence of infection and the spectrum of associated pathogens. - Results - 152 patients received an abdominal wall patch (GORE-TEX®). Predictive factors included birth weight, gestational age, gender, time of diagnosis of CDH, defect size, type of hernia, and liver-up. The majority of all patches which had to be explanted, was removed within one year, resulting in shorter operation time (median: 99.5 min) compared to late removal (>365 days, median: 144.5 min, p < 0.0163). Complication rates were comparable in both groups (early: 26.87 %, late: 25.93 %, p = 0.9257). Most common reasons for patch removal were: infections (50.00 %), elective removal (28.72 %) and removal concomitantly during another surgery (13.83 %). The most common pathogen in infected patches was Staphylococcus aureus. - Conclusion - The study suggests that early patch removal is associated with a shorter surgery time and does not lead to an increased rate of complications. In cases of patch infection, empirical antibiotic therapy targeting staphylococcal bacteria is recommended in the absence of an antibiogram. It may provide pediatricians and pediatric surgeons with guidance regarding the postoperative management of abdominal wall patches.
Online veröffentlicht: 28. Dezember 2024, Artikelversion: 7. Januar 2025
Gesehen am 03.07.2025